PENGARUH ECONOMIC VALUE ADDED (EVA) DAN RETURN ON ASSET (ROA) TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI - Imas Fatimah; Tami Sriwijati (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2022)
Shares are a sign of a statement of capital/fund ownership in a company. The share price has its own important value for the company, if the share price of a company is high this provides an opportunity for the company to get additional investment from investors from its share price increase This research aims to find out if Economic Value Added (EVA) and Return On Asset (ROA) affect the share price of property and real estate companies listed on the Indonesia Stock Exchange. This research uses quantitative motode. The data types in this study are secondary data and samples used by 11 property and real estate companies with nonprobability Samplingand Purposve Sampling sampling techniques. Its analytical techniques are used with classic assumption tests, multiple linear regression analyses, and hypothesis tests consisting of determination coefficient tests (R2) partial testing (t tests), and significance tests (F tests). in this study assisted with spss v.22 application. The results showed that partially Economic Value Added (EVA) had a significant effect on the share price, while Retrun On Asset (ROA) partially had a significant effect on the share price. Based on simultaneously suggesting that Economic Value Added (EVA) and Retrun On Asset (ROA) together have a significant effect on the share price.